Diseño de adaptaciones curriculares en la Educación Superior para estudiantes con discapacidad física de la Universidad Nacional de Loja, período 2024. - Silva Pauta, Tania Mariela (2024)
The design of curricular adaptations in Higher Education for students with physical disabilities at the National University of Loja, has enabled the compliance with the present institutional and national regulations to guarantee inclusive education. This research was developed at the National University of Loja during the period March-August 2024, its objectives were to characterize the design of curricular adaptations by teachers, to identify challenges and obstacles faced by teachers when applying curricular adaptations, and to make a proposal aimed at overcoming this problem. To this end, a descriptive and cross-sectional methodology was used, along with a mixed approach, since quantitative and qualitative information was collected, integrated and analysed applying the inductive, deductive, analytical, and synthetic methods and thus the techniques of the survey aimed at teachers and semi-structured interviews with University Welfare personnel. The results found evidence that 50.9% of teachers have not received specific training on curricular adaptations, 53% develop interdisciplinary collaboration, 37.4% consider the deficiency of specific training as a main challenge, and 47.4% point to the absence of institutional guides as an important barrier; Based on these results a proposal was made, focused on the making of a strategies manual to design a curricular adaptations for students with physical disabilities, such manual is structured for the components of learning in contact with the teacher, and it is experimental, practical and autonomous; It will also enhance the teaching-learning process of students with physical disabilities, consequently ensuring their academic success.